Soil erodibility factor oxisols in Rio Grande do Sul - Dedecek, Renato Antonio; Cabeda, Mário Sérgio Vaz (Pesquisa Agropecuaria Brasileira, 2014)
The soil-erodibility factor of Oxisols (Latosol) in Rio Grande do Sul, Brazil, was predicted through the study of five soil physical parameters. The soil presented low K values and high inherent resistance to rainfall erosion. The interne erosion showed by these soils is due to poor soil management systems, and to climatic and topographic factors.